Differential transport function of lymphatic vessels in the rat tail model and the long-term effects of Indocyanine Green as assessed with near-infrared imaging - Weiler, Michael; Dixon, J. Brandon (Frontiers in Physiology, 2013)
Introduction: Near-infrared (NIR) imaging has emerged as a novel imaging modality for assessing lymphatic function in vivo. While the technique has provided quantitative data previously unavailable, questions remain in regards to the spatiotemporal capabilities of the approach. We address three of the more important issues here using the rodent tail, one of the most widely utilized in vivo model systems in the lymphatic literature. Specifically we demonstrate 1) the transient vs. steady state response of lymphatics to tracer injection, 2) the functional characteristics of multiple collecting vessels draining the same tissue space in parallel, and 3) the long-term consequences of fluorescent tracers on lymphatic function to repeated functional measurements. Methods: Rat tails were imaged with NIR and metrics of function were calculated for both collecting vessels that drain the tail. A nitric oxide donor cream (GTNO) was applied to the tail. Additionally, two different NIR dyes, indocyanine green (ICG) and LI-COR IRDye 800CW PEG, were utilized for function imaging at the time of initial injection and at 1, 2, and 4 week follow-up time points after which both draining lymph nodes were harvested. Results and Discussion: Significant differences were found between the two collecting vessels such that the vessel first showing fluorescence (dominant) produced enhanced functional metrics compared to the second vessel (non-dominant). GTNO significantly reduced lymphatic function in the non-dominant vessel compared to the dominant. ICG remained visible in the tail for 2 weeks after injection and was accompanied by significant losses in lymphatic function and enlarged draining lymph nodes. The Licor tracer also remained visible for 2 weeks. However, the dye produced significantly lower effects on lymphatic function than ICG, and lymph nodes were not enlarged at any time point, suggesting that this may be a more appropriate contrast agent for longitudinal lymphatic imaging.